High temperature fatigue behaviour in an advanced nickel based superalloy: The effects of oxidation and stress relaxation at notches - Martin Bache (Theoretical and Applied Fracture Mechanics, 2016)
The low cycle fatigue performance of the nickel based superalloy RR1000 was investigated under a variety of load waveforms at high temperature, employing a double edge notch geometry under load control. Experiments on a plain cylindrical specimen design under strain control were later performed to simulate the constrained conditions at the root of the notch in order to characterise the interaction between surface constituents and the environment. A significant fatigue debit was demonstrated under both load/strain scenarios when superimposing a dwell period at the minimum point of the cycle. This debit was attributed to a reduction in fatigue crack initiation life resulting from oxidation damage which subsequently cracks under cyclic tension together with a modification to the mean stress through cyclic stabilisation. The same dwell period superimposed at the peak of the cycle was essentially benign for excursions under strain control loading.